HYDROGEOLOGICAL IDENTIFICATION OF THE WELARAN WATERSHED KARANGSAMBUNG BASED ON DESCRIPTIVE-QUALITATIVE METHOD - Nandian Mareta; Rachmat Fajar Lubis; Boy Yoseph CSS Syah Alam; Mohammad Sapari Dwi Hadian (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2021)
The Welaran watershed in the Karangsambung area is hydrogeologically interesting because of its morphology, “U” shaped morphology like an amphitheater with the lithology consisting of tertiary to quarternary rocks. The character of Welaran river is an intermittent river that watery during the rainy season and dry during the dry season. This study intended to identify and determine the general hydrogeological condition of the Welaran watershed on a scale of 1:20.000. This study applies a descriptive-qualitative research method. The steps used are hydrogeological analysis and water balance. The results obtained indicate that the hydrogeological conditions of the area affect the character of the rivers in t